2022
DOI: 10.1093/bjsopen/zrab151
|View full text |Cite
|
Sign up to set email alerts
|

Use of intraoperative parathyroid hormone measurements during parathyroidectomy to predict postoperative parathyroid hormone levels in patients with renal hyperparathyroidism: meta-analysis

Abstract: Background Several studies have reported on the use of intraoperative parathyroid hormone (ioPTH) measurements during parathyroidectomy (PTX) for renal hyperparathyroidism (rHPT), but there is no consensus on whether it is helpful and, if so, what protocol should be used. Therefore, the literature was systematically reviewed to assess a correlation between ioPTH and early postoperative parathyroid hormone (PTH) levels in patients undergoing PTX for rHPT, separately for those on dialysis and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 69 publications
(163 reference statements)
0
2
0
Order By: Relevance
“…Moreover, intraoperative PTH (ioPTH) monitoring provides a more precise profile of the PTH level (51). Von Beek et al (52) found that there was a strong correlation between ioPTH and early postoperative PTH levels, indicating that ioPTH was a potentially useful index for predicting surgical effectiveness. In patients with functioning allografts, ioPTH levels 10 min and 20 min after resection of the parathyroid glands were equivalent to 2.6 times and 2.3 times the post-operative PTH levels, respectively, and were considered to possibly fall within the expected target range (52).…”
Section: Relatively Limited Parathyroidectomy (Subtotal Parathyroidec...mentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, intraoperative PTH (ioPTH) monitoring provides a more precise profile of the PTH level (51). Von Beek et al (52) found that there was a strong correlation between ioPTH and early postoperative PTH levels, indicating that ioPTH was a potentially useful index for predicting surgical effectiveness. In patients with functioning allografts, ioPTH levels 10 min and 20 min after resection of the parathyroid glands were equivalent to 2.6 times and 2.3 times the post-operative PTH levels, respectively, and were considered to possibly fall within the expected target range (52).…”
Section: Relatively Limited Parathyroidectomy (Subtotal Parathyroidec...mentioning
confidence: 99%
“…Von Beek et al (52) found that there was a strong correlation between ioPTH and early postoperative PTH levels, indicating that ioPTH was a potentially useful index for predicting surgical effectiveness. In patients with functioning allografts, ioPTH levels 10 min and 20 min after resection of the parathyroid glands were equivalent to 2.6 times and 2.3 times the post-operative PTH levels, respectively, and were considered to possibly fall within the expected target range (52). With accurate monitoring, an acute decline in renal function after parathyroidectomy can be avoided and a stable renal function can be achieved throughout the 1-year followup (51).…”
Section: Relatively Limited Parathyroidectomy (Subtotal Parathyroidec...mentioning
confidence: 99%